Uniformisation des taux de profit et hypothèse sectorielle - Chiavelli, Alain; Rainelli, Michel (L'Actualité économique)

(untitled) (HEC Montréal, 1977)
AbstractThe hypothesis of an equalization of sectorial rates of profit has an important role to play in the economic theory. Though it has been formulated a long time ago (A. Smith, D. Ricardo…), now as a definite principle (with its mechanism) and now as a postulate, it is however contradicted by statistical observation. There have been various answers to this problem. We propose to study it in a new light, emphasizing that the formulation of this "law" as well as its empirical evidence are registered within the traditional framework of activity sector. Then, we have to think about the latter as it has a fundamental role to play. But the activity sector is no longer a homogeneous category, for firms can considerably differentiate the conditions (technological and financial ones) of capital allowance, independently of any reference to the notion of product. Then, we must think over this problem, no longer wondering where this allowance of the capital is produced, but how. This brings us to propose the elaboration of a new classification of the firms, that leads to an analysis at an "intermediary level" other than the insufficient level that results from the division of the economy into activity sectors.